2016
DOI: 10.3390/ijerph13111071
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Governing Factors of Variability in Nocturnal Boundary Layer Height Based on Elastic Lidar in Wuhan

Abstract: The atmospheric boundary layer (ABL), an atmospheric region near the Earth’s surface, is affected by surface forcing and is important for studying air quality, climate, and weather forecasts. In this study, long-term urban nocturnal boundary layers (NBLs) were estimated by an elastic backscatter light detection and ranging (LiDAR) with various methods in Wuhan (30.5° N, 114.4° E), a city in Central China. This study aims to explore two ABL research topics: (1) the relationship between NBL height (NBLH) and nea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 40 publications
2
6
1
Order By: Relevance
“…The concentration of PM 2.5 at 0.2 km has the highest value in the winter (93.7 µg/m 3 ), followed by the autumn and summer (80.3 and 75.8 µg/m 3 , respectively), and lowest in the spring (53.5 µg/m 3 ). This finding is similar to the surface observation results (Wang et al, 2016). The PM 2.5 concentration decreases gradually with the height increases.…”
Section: Vertical Evolution Of Pm 25 and Tfsupporting
confidence: 92%
“…The concentration of PM 2.5 at 0.2 km has the highest value in the winter (93.7 µg/m 3 ), followed by the autumn and summer (80.3 and 75.8 µg/m 3 , respectively), and lowest in the spring (53.5 µg/m 3 ). This finding is similar to the surface observation results (Wang et al, 2016). The PM 2.5 concentration decreases gradually with the height increases.…”
Section: Vertical Evolution Of Pm 25 and Tfsupporting
confidence: 92%
“…The concentration of PM2.5 at 0.2 km has the highest value in the winter (93.7 ug/m 3 ), followed by the autumn and summer (80.3 and 75.8 ug/m 3 , respectively), and lowest in the spring (53.5 ug/m 3 ). This finding is similar to the surface observation results (Wang et al, 2016). The PM2.5 concentration decreases gradually with the height increases.…”
Section: Vertical Evolution Of Pm25 and Tfsupporting
confidence: 92%
“…What is more, numerous epidemiological studies have indicated that the suspended particles in the atmosphere, especially those with an aerodynamic diameter not larger than 2.5 µm (PM 2.5 ), would produce serious adverse effects on human bodies, hence increasing deaths from cardiovascular and respiratory diseases and even lung cancer [7,8]. As such, aerosols have drawn considerable concern [9,10,11]. In recent years, numerous studies have been conducted to investigate the formation mechanisms of aerosol pollution, and some of them implied the important role of relative humidity ( RH ) in this issue because of the aerosol hygroscopicity [12,13].…”
Section: Introductionmentioning
confidence: 99%